Association among objective and subjective sleep duration, depressive symptoms and all-cause mortality: the pathways study - Yuan Zeng; Tanshu Liu; Rui Qiu; Qingqing Lian (BMC Psychiatry)
Abstract Background Sleep deprivation and overload have been associated with increased risks of both depression and mortality. However, no study has quantitatively compared the effects of objective and subjective sleep duration on mortality or examined the mediating role of depressive symptoms in these associations. Methods Utilizing data from the NHANES 2011–2014, this study employed structural equation modeling (SEM) to explore the impact of depressive symptoms, measured by Patient Health Questionnaire (PHQ-9) scores, on the relationship between both objective and subjective sleep durations and all-cause mortality. Results The study included 7838 participants, comprising 4392 women (55.96%) with a mean age of 46.51 (0.46) years. Over a median 6.83-year follow-up, 582 deaths occurred. The restricted cubic spline curves demonstrated a J-shaped relationship between objective sleep duration and the all-cause mortality risk, and a U-shaped relationship between subjective sleep duration and the all-cause mortality risk. SEM analysis revealed that when subjective sleep duration was < 7 h/day, the indirect effect of sleep duration on all-cause mortality was − 0.013 (P = 0.003), and the mediation proportion of PHQ-9 scores was 40.63%. When objective sleep duration ≥ 7 h/day, the indirect effect of sleep duration on all-cause mortality was 0.003 (P = 0.028), and the mediation proportion of PHQ-9 scores was 2.10%. Conclusions The study confirmed a J-shaped and a U-shaped correlation for objective and subjective sleep duration with mortality risk. Depressive symptoms significantly mediated the association between shorter subjective sleep duration and mortality. This suggests that there is a need to focus on the co-morbidity of subjective sleep deprivation and depression.